Anti-tumor activity of BML Proteases in Breast Cancer, Prostate Cancer and Cervical Cancer by Up-regulation of p53 gene, NF-kB and COX-2 expression through targeting MAPK Pathway - G, Swaroop; Viswanathan, Geetha (International Journal of Pharmacology and Toxicology, 2013)
Chemo impediment impels the quest for moreover single targeted or brew of multi-targeted agents. BML proteases, potential agent in this regard, is a pharmacologically active compound, present in stems and fruits of Ananas comosus, endowed with anti-inflammatory, anti-invasive and antimetastatic properties. BML protease is a complex or proteolytic enzymes. These proteolytic enzymes are paraphernalia that promise an impressive number of medical and therapeutic uses, particularly as anti-tumor agents (Swaroop G et al. 2013, p.80). BML proteases is a pharmacologically active compound, present in stems and immature fruits of pineapples (Ananas comosus), which has been shown to have anti-edematous, anti-inflammatory, anti-thrombotic and anti-metastatic properties (Swaroop G et al. 2013, p.80). In the present study anti-tumorigenic activity of BML was recorded in HeLa, MCF 7 and PC3 cell lines. Results showed that BML proteases application delayed the onset of tumorigenesis and reduced the cumulative number of tumors, tumor volume and the average number of tumor cells. To establish a cause and effect relationship, we targeted the proteins involved in the cell death pathway. BML proteases treatment resulted in up-regulation of p53 gene and subsequent activation of caspase 3 and caspase 9 with concomitant decrease in anti-apoptotic protein Bcl-2 in cancer cells targeting intrinsic pathway of apoptosis. BML treatment attenuated phosphorylation of extracellular signal regulated protein kinase (ERK1/2) and mitogen-activated protein kinase (MAPK). Taken together, we conclude that BML induces apoptosis-related proteins by blocking the MAPK kinase signaling in tumor cells, which may account for its anti-tumorigenic effects. Flow cytometry studies were carried out for the study of cell cycle progression.